Development of Wireless Powered Ionic Polymer Metal Composites (Ipmc) Devices for Biomedical Application S - Cheong, Hau Ran (2018)
Ionic polymer metal composite IPMC is an ionic electroactive polymer (EAP) that can be actuated at a low voltage , fast response and miniaturized, therefore, attracts significant interest that h as led to extensive investigations, especially for biomedical application s . Conventional battery powered and wired interfaced IPMC actuator has limited mobility and poses the risk of battery leakage which is hazardous to human health. This project proposed an IPMC soft actuator that is controlled and powered in a wireless manner using magnetic resonant coupling as an effort to solve the mentioned constraint. The IPMC cantileve r deflects when the external magnetic field (generated by the transmitter circuit) matches the resonant frequency of the LC receiver circuit (with IPMC actuator The proposed wirelessly powered IPMC actuator was demonstrated in biological cell manipulation application. A single active finger IPMC-based microgripper was fabricated by integrating the IPMC actuator to the developed planar resonant LC receiver and DC rectifier circuits. The fabricated prototype shows a maximum IPMC deflection of 0.765 mm (activation force of 0.17 mN) at the RF power of 0.65 W with 3.5 VDC supplied from the LC receiver circuit at the resonant frequency of ~13.6 MHz. Three repeated ON-OFF wireless activation cycle was performed with the reported cumulative deflection of 0.57 mm. The cumulative deflection was increased to 1.17 mm, 1.19 mm and 1.24 mm for three different IPMC actuator samples respectively at 5 VDC supplied. As a proof of concept, fish egg was used to represent the biological cell manipulation operation. The microgripper successfully gripped the fish egg sample without creating any damages. Apart from the wireless ly powered microgripper, the wireless feature has been extended as an implantable drug delivery device. A 183 μm thick IPMC cantilever valve was attached with an embedded LC resonant circuit to wirelessly control the actuator when the field frequency is tuned to 25 MHz. Experimental characterization of the fabricated actuator showed a cumulative cantilever deflect ion of 160 μm for three repeated RF ON OFF cycles at 0.6 W input power. The device was loaded with dye solution and immersed in DI water to demonstrate wireless drug release. Qualitative result shows the successful release of the dye solution from the devi ce reservoir. The release rate can be controlled by tuning the RF input power. A maximum average release rate of ~0.1 μl/s was achieved. I n vitro study with human tumor cells (HeLa) has been further conducted to demonstrate the proof of concept of the dev eloped device. Exclusively, the effectiveness of developed wirelessly powered IPMC actuator as biomedical devices has been validated with its effectiveness in soft microgripper and drug delivery application.